CONTROLLING BIOFOULING FORMATION IN MEMBRANE DISTILLATION - Ariel, Jonathan
Seawater desalination is one of the methods use to overcome the shortage of clean water by processing sea water into fresh water. One of the newest seawater desalination technologies is vapor pressure driven membrane such as membrane distillation. However, using seawater as the feed will stimulate the formation of biofouling in MD. This is caused by the microorganism living in the seawater attached on membrane surface and creating biofilm, so the performance of MD will decrease with time. Based on previous researches about controlling biofouling formation in pressure driven membrane, biofouling could be controlled by chemical and physical treatment. Some of these methods have not been studied for controlling biofouling in MD. Therefore, a research is conducted to study the appropriate treatment for controlling biofouling formation in MD with VMD (Vacuum Membrane Distillation) configuration using artificial seawater which contains Pseudomonas aeruginosa as feed. Chemical treatment is done by using NaOH 2%, and physical treatment is done by air-backwashing. The research is carried out in 6 hour experiment, with frequency and duration variation, as well as air pressure used in air-backwashing. To investigate the effect of every treatment, several analysis is conducted such as flux analysis, conductivity analysis, morphology of the membrane, membrane hydrophobicity, and biofouling formation. The result obtained from SEM analysis did not show the presence of biofilm on membrane, which indicates that biofouling is formed due to the presence of Soluble Microbial Products (SMP). Besides, the results obtained from this research are chemical cleaning using NaOH effectively removed biofouling when the treatment is done 30 minutes every 4 hours. Physical treatment using air backwashing effectively removed biofouling when the treatment is done 10 seconds every 4 hours with air pressure is 1 bar. Chemical treatment is more effective in controlling biofouling formation than physical treatment. The treatment should be done properly, because it can accelerate membrane wetting if it is done too often.